ROLE OF THE STATE IN THE DISTRIBUTION AND REDISTRIBUTION OF CASH AND AGRICULTURAL RESOURCES IN THE REGIONS OF THE RUSSIAN FEDERATION - & et al., Nagoev (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The article discusses the distribution of financial resources with a preference   for land assets and production of deep processed products with the highest added value, which simultaneously increases the incomes of producers and improves government revenues by increasing tax receipts. It is noted that the progressive development of agriculture depends on the technical modernization of the industry, which also requires investment. Therefore, it is necessary to subsidize the modernization and reconstruction of fixed assets - granaries, greenhouses. Potential profit, which will become an important component of investment, can give a boost to the investment activity. An analysis was carried out on the conceptual foundations of building economic relations in modern agricultural production. The conditions for the agricultural development have been assessed, and critical insights on mechanisms for implementing state and regional target programs have been provided. In terms of a systemic approach to the State economic management, the economic processes should be considered as a system of financial relations that interacts with other systems. In this regard, the paper presents a model that reflects the conceptual framework for managing financial flows. This model provides an overview of managing economic processes, and may take into account many elements and factors.